Criterios para la elaboración de un currículum intercultural en Melilla un estudio multimétodo - Arroyo González, Rosario (Revista Española de Pedagogía, 2016)
This article tries to illustrate, through an investigation, the methodological possibilities of the complementary education (both, from quantitative and qualitative perspectives) applied to a multicultural context. The investigation presented in this article was carrid out in the multicultural context of the town of Melilla. The author aims to lay the foundations of the design of an Islamic-occidental intercultural curriculum based on the common values of the two cultures. It is also a main purpose of the article to present the design of this investigation, putting the emphasis on the objectives, hypothesis, variables, procedures and techniques of control (triangulation and saturation). Finally, the author presents the synthesis of the most interesting results
Keywords: Revista Española de Pedagogía; currículum; Melilla